Keeping it in the family: understanding the negotiation of intergenerational transfers for entry into homeownership. Issue 8 (22nd October 2021) - Cook, Julia
Abstract: House prices have risen sharply in most Australian capital cities in recent years. Due to Australia's strong identity as a homeowning nation and the related tendency towards entering the housing market within the 25–34 age bracket the impact of rising property prices has been distinctly generational, with young adults experiencing significant challenges entering the property market. A growing number of studies have identified financial transfers within families as a means through which entry into the housing market is facilitated for young adults. This article contributes to this discussion by drawing on interviews conducted with 29–30-year-old homeowners in Australian capital cities to address the negotiation of intergenerational support. Specifically, it considers how the conditions under which transfers are received may impact upon the ways in which they are subsequently understood. In so doing this article contributes to growing international debate about intersubjective understandings of intergenerational transfers.